Behavioural public policy for natural disaster preparedness and the role of economic experiments - Peter John Robinson; W. J. Wouter Botzen (Humanities & Social Sciences Communications)
Natural disaster losses are increasing both in their frequency of occurrence and severity of impacts worldwide due to climate change and socio-economic development in disaster-prone regions. In addition to public sector investments in disaster protection infrastructure, individuals can manage these losses by implementing disaster risk reduction measures at the household level. However, a host of systematic cognitive biases may prevent the taking of cost-effective forms of risk reduction by individuals. Behavioural public policies have been proposed as a way to address these biases in order to stimulate societal natural disaster preparedness. This article highlights the role of economic experiments for developing behavioural public policies that promote disaster risk reduction actions. Based on a review of the state-of-the-art of the experimental literature, several promising directions for further research in the field are outlined. That is, avenues for further experimental research in behavioural public policy are identified. We find that more experimental research is needed to examine whether: (1) behavioural public policies can complement conventional forms of economic policy that alter financial incentives; (2) methodological advancements in the field of experimental economics can be used to further develop behavioural policies aimed at triggering natural disaster preparedness; and (3) behavioural policies are useful for addressing various under-researched field observations and realities faced by individuals at risk of natural disasters.